2015
DOI: 10.1063/1.4913300
|View full text |Cite
|
Sign up to set email alerts
|

Temperature dependence of anisotropic magnetoresistance in antiferromagnetic Sr2IrO4

Abstract: We report point-contact measurements of anisotropic magnetoresistance (AMR) in a single crystal of antiferromagnetic (AFM) Mott insulator Sr2IrO4. The point-contact technique is used here as a local probe of magnetotransport properties on the nanoscale. The measurements at liquid nitrogen temperature revealed negative magnetoresistances (MRs) (up to 28%) for modest magnetic fields (250 mT) applied within the IrO2 a-b plane and electric currents flowing perpendicular to the plane. The angular dependence of MR s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

2
23
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 31 publications
2
23
0
Order By: Relevance
“…5a gives a band-gap change of about 0.34 meV. Furthermore, the switching threshold I c exhibits a clear magnetic field dependence I c (μ 0 H), which correlates with the point-contact R(μ 0 H) magnetoresistance [13] observed at zero bias (compare Figs. 5b and 5c).…”
mentioning
confidence: 62%
See 4 more Smart Citations
“…5a gives a band-gap change of about 0.34 meV. Furthermore, the switching threshold I c exhibits a clear magnetic field dependence I c (μ 0 H), which correlates with the point-contact R(μ 0 H) magnetoresistance [13] observed at zero bias (compare Figs. 5b and 5c).…”
mentioning
confidence: 62%
“…The increase in I c (μ 0 H) with increasing field correlates with the decrease in R(μ 0 H), but their relative changes are quite different and cannot be explained by a field-independent critical voltage V c =I c R. Previous studies suggested that lattice distortions in SIO may cause a magnetoresistive effect due to a strong spin-orbit coupling [7,8,13] . The correlations between the magnetoresistance and resistive switching observed in our present work suggest that the magnetoresistive phenomenon in SIO could originate from the band structure modifications associated with the field-induced lattice distortions.The interplay between magnetism and electron transport may be further illustrated by studying the effects of bias on SIO magnetoresistance (MR) [13] . The MR was previously [13] associated with a crystalline component of anisotropic magnetoresistance (AMR) and the effects of applied field on the canting of antiferromagnetically coupled moments in SIO.…”
mentioning
confidence: 99%
See 3 more Smart Citations